2011
DOI: 10.1002/anie.201100332
|View full text |Cite
|
Sign up to set email alerts
|

Robust and Open Tailored Supramolecular Networks Controlled by the Template Effect of a Silicon Surface

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
94
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(97 citation statements)
references
References 36 publications
3
94
0
Order By: Relevance
“…Despite their relatively weak nature, the molecule-substrate interactions have a strong bearing on the adsorption of molecules [36][37][38][39][40][41]. Detailed experimental and theoretical studies have revealed that the tendency of molecules in a two-dimensional monolayer to comply with the registry of the substrate lattice can result in significant changes in intermolecular interactions when compared with their self-assembly in three-dimensional crystals [36].…”
Section: Role Of the Substrate And The Mediummentioning
confidence: 99%
“…Despite their relatively weak nature, the molecule-substrate interactions have a strong bearing on the adsorption of molecules [36][37][38][39][40][41]. Detailed experimental and theoretical studies have revealed that the tendency of molecules in a two-dimensional monolayer to comply with the registry of the substrate lattice can result in significant changes in intermolecular interactions when compared with their self-assembly in three-dimensional crystals [36].…”
Section: Role Of the Substrate And The Mediummentioning
confidence: 99%
“…10 Single 11,12 and multicomponent 1,[13][14][15][16] self-assembled porous nanoarchitectures can be achieved through hydrogen bonding. Building blocks based on molecule having carboxyl groups (COOH) are especially interesting because these groups can form 2 H-Bonds (O-H· · · O).…”
Section: Strong Intermolecular Interactions Are Required To Stabilizementioning
confidence: 99%
“…7−11 In twodimensional (2D) self-assembled molecular networks (SAMNs) the substrate serves as physical support but can also play an important role in driving formation of a specific pattern. As such, the template effect can be exploited to reinforce or work against 12 the inherent molecular symmetries. Ordered self-assembled 2D nanostructures are typically observed when the mobility of single molecules is sufficiently high to allow them to diffuse and achieve a configuration desirable for attractive, stabilizing intermolecular interactions.…”
Section: ■ Introductionmentioning
confidence: 99%